Broken hegemonies - Vahabzadeh, Peyman (The journal for cultural and religious theory, 2004)
A review of Reiner Schürmann, Broken Hegemonies, translated by Reginald Lilly, Bloomington & Indianapolis: Indiana University Press, 2003, 692 pp.